Hacking agency: Apps, autism, and neurodiversity. - Demo, Anne Teresa (Quarterly Journal of Speech, 2017)
This essay examines the complex relationship between agency and technology. I compare autism apps developed by Samsung and Toca Boca and show that while app marketing retains a human-centered notion of agency, user–app interactions distribute agency through a constellation of human and nonhuman actors. The divergence between marketing and use, as well as critiques about agency and technology within disability studies, motivates my argument for hacking agency. Whether in computer or knowledge networks, hacking is a critical process that exploits information silos for particular ends. In this essay, I seek to broaden notions of rhetorical capacity and challenge narrow approaches to intentionality so as to facilitate the attribution of agency across the neurological spectrum.